Author Correction: Graphene perfect absorber of ultra-wide bandwidth based on wavelength-insensitive phase matching in prism coupling (Scientific Reports, (2019), 9, 1, (11967), 10.1038/s41598-019-48501-w) - Lee, Sangjun; Heo, Hyungjun; Kim, Sangin (Scientific Reports, 2019)
A supplementary information containing Figures S1 and S2, and equations S1-S9, was omitted from the original version of this Article. This has been corrected in the HTML and PDF version of the Article.